THE LEGITIMACY OF PURI AGUNG KERAMBITAN TABANAN TOWARDS THE CULTURAL DEGRADATION CRISIS OF THE OKOKAN TRADITION - Riza Wulandari; I Gusti Ngurah Nyoman Bagiarta; Nyoman Ayu Nila Dewi (Sosiohumaniora, 2022)
The progress of the times has an impact on the behavior of memory decline regarding culture and profane values so that it has an impact on the ambiguity of the future of culture itself in this case is the tradition of the Okokan performance. This study aims to explore the role of power (legitimacy) of Puri Agung Kerambitan Tabanan on the Okokan Tradition to the cultural degradation that occurred. The method used in this study is a qualitative research method using two types of data sources, namely primary and secondary as well as data collection in the form of observations, interviews and literature studies (literature). Talcot Parson on Structural Functionalism was used in honing this research. Based on the data in the field, it was found that the role of the legitimacy or power of Puri Agung Kerambitan Tabanan was to first form a new group of the young generation of okokan art to be included in every event / activity of the castle. Second, support and take an active role in okokan performing arts groups. This role that has been carried out still requires an understanding strategy to be disseminated to meet the needs disposition. In line with Talcott Parson’s thinking that the disposition of needs can be achieved through a physical system (environment) and a personality system that can be done through socialization in the form of disseminating information through digital media and social control through awig-awig published by stakeholders, both Heritage Village and Puri Agung Kerambitan.